1997
DOI: 10.1063/1.118912
|View full text |Cite
|
Sign up to set email alerts
|

Observation of nanocrystalline diamond in diamondlike carbon films deposited at room temperature in electron cyclotron resonance plasma

Abstract: Low temperature deposition of nanocrystalline silicon carbide films by plasma enhanced chemical vapor deposition and their structural and optical characterization J. Appl. Phys. 94, 5252 (2003); 10.1063/1.1609631 Hydrogen content and density in nanocrystalline carbon films of a predominant diamond character J. Appl. Phys. 94, 4589 (2003); 10.1063/1.1603951Modeling and analysis of hydrogen-methane plasma in electron cyclotron resonance chemical vapor deposition of diamond-like carbon Evaluation of the ion bomba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(14 citation statements)
references
References 6 publications
1
12
0
1
Order By: Relevance
“…Lattice fringes clearly appeared in the enlargement of the left-hand side of the sample, as shown in Fig. 6 sizes of nanocrystalline diamond films previously reported by several authors [15,23,29,78], in which the grain sizes were found to be in the range 3-50 nm.…”
Section: Eels Mappingmentioning
confidence: 60%
See 1 more Smart Citation
“…Lattice fringes clearly appeared in the enlargement of the left-hand side of the sample, as shown in Fig. 6 sizes of nanocrystalline diamond films previously reported by several authors [15,23,29,78], in which the grain sizes were found to be in the range 3-50 nm.…”
Section: Eels Mappingmentioning
confidence: 60%
“…While a microwave plasma is most commonly used for the PE-CVD of diamond films, ECR plasma is the only plasma used for diamond deposition at pressures below 1 Torr [27][28][29]. Bozeman et al [30] reported diamond deposition at 4 Torr using a planar ICP, and there are a few reports that describe the synthesis of diamond by lowpressure ICP.…”
Section: Low-pressure Pe-cvdmentioning
confidence: 99%
“…For microwave plasma deposition technology, electron cyclotron resonance plasma could deposit diamond films at pressure of some hundredths to thousandths torr. Zarrabian et al concluded that they observed NCD film with pressure of 2.7 mTorr [2]. Kouzuma et al also reported diamond film could be deposited at pressure of 1 mTorr [3].…”
Section: After William G E Synthesized Diamond By Chemical Vapor Dementioning
confidence: 95%
“…These films can be deposited at lower temperatures compared to diamond. Recent work shows that if electron cyclotron resonance plasma is used, DLC films obtained at room temperature can contain nanocrystalline cubic or hexagonal diamond [19]. Amorphous DLC (a-C:H) films can be crystallized by laser treatment producing a mixture of diamond nanocrystals of 2-7 nm in size and graphite particles of 2-4 nm in size.…”
Section: Nanocrystalline Diamond and Dlc Filmsmentioning
confidence: 99%